A LysM domain-containing protein TaLysM1-A confers salinity and drought tolerance in transgenic Arabidopsis - Deepika (Plant physiology and biochemistry : PPB, 2025)
Copyright © 2025 The Authors. Published by Elsevier Masson SAS.. All rights reserved.